Broadband circularly polarised square slot antenna fed by coplanar waveguide. Issue 16 (1st August 2013) - Liu, Y.W.; Hsu, P.
Abstract : A broadband circularly polarised square slot antenna fed by a coplanar waveguide (CPW) from a corner of the slot is proposed. A check‐shaped strip with its vertex connected to the protruded signal strip of the CPW is used to achieve circular polarisation. The measured 3 and 1 dB axial ratio bandwidths are 48 and 21.3%, respectively, and the input impedance bandwidth (| S 11 | ≤ − 10 dB) is 73.9%, which covers the entire circular polarisation band.